2018
DOI: 10.3389/fimmu.2018.00139
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Mediated Inflammation Promotes Subclinical Atherosclerosis in Recent-Onset Psoriatic Arthritis Patients without Conventional Cardiovascular Risk Factors

Abstract: Studies on the inflammatory burden in recent-onset psoriatic arthritis (PsA) patients without conventional cardiovascular risk factors (CVRFs) are not available. This preliminary study focuses on cardiovascular risk in cutaneous psoriasis (CPs) and recent-onset PsA patients. Blood biochemistry (glucose, cholesterol, uric acid, lipid profile and apolipoprotein B) was analyzed using standard kits. Proatherogenic inflammation markers, C-reactive protein (CRP) and interleukin-6 (IL-6), and endothelial activators m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 62 publications
3
16
1
Order By: Relevance
“…Recently, Kolliker Frers et al have demonstrated that pro-atherogenic inflammation marker C-reactive protein (CRP) and soluble intercellular adhesion molecule-1 levels are increased also in psoriatic patients with no CV history or traditional CV risk factors, compared with healthy subjects, as well as in patients with recent-onset PsA, even in the absence of CV risks. These data reinforce the concept that that the degree of atherosclerosis tendency might be related to the amount of the inflammatory psoriatic burden and highlight the importance of primary prevention in Pso also in those psoriatic patients with no history of CV events ( 24 ).…”
Section: Psoriasis and Cardiovascular (Cv) Eventssupporting
confidence: 83%
“…Recently, Kolliker Frers et al have demonstrated that pro-atherogenic inflammation marker C-reactive protein (CRP) and soluble intercellular adhesion molecule-1 levels are increased also in psoriatic patients with no CV history or traditional CV risk factors, compared with healthy subjects, as well as in patients with recent-onset PsA, even in the absence of CV risks. These data reinforce the concept that that the degree of atherosclerosis tendency might be related to the amount of the inflammatory psoriatic burden and highlight the importance of primary prevention in Pso also in those psoriatic patients with no history of CV events ( 24 ).…”
Section: Psoriasis and Cardiovascular (Cv) Eventssupporting
confidence: 83%
“…Elevated levels of sCD54 and MIF in the serum of patients with psoriasis and control over their dynamics have prognostic significance in determining both the severity of the disease and the effectiveness of the therapy. The obtained data are consistent with the results of other researchers, indicating the value of serum markers sCD54 (31) and MIF (32, 33) in the pathogenesis of psoriasis, and can be considered as potential biomarkers and targets for immunomodulating therapies for psoriasis. Standardized serum markers measurement is available for clinical use and analysis of secreted protein after treatment by immunomodulators would offer a prognostic factor of the therapy effectiveness.…”
Section: Resultssupporting
confidence: 91%
“…Regarding SLE, data is more limited, but studies have shown increased levels of certain soluble endothelial damage biomarkers, such as ICAM-1 and thrombomodulin (TM) in SLE women and VCAM-1 in patients with lupus nephritis [ 126 , 127 ] Similarly, AS studies indicate that increased levels of ICAM-1, TM and IL-6, as well as increased ADMA serum concentrations are not correlated however with disease activity [ 128 , 129 , 130 ]. In PsA, both ICAM-1 and VCAM-1 levels have been found to be increased compared to controls and ICAM and IL6 were correlated with Cimt [ 131 , 132 ].…”
Section: Immunological Mechanismsmentioning
confidence: 99%